Genotype-Specific Steroid Profiles Associated With Aldosterone-Producing Adenomas. Issue 1 (January 2016) - Williams, Tracy Ann; Peitzsch, Mirko; Dietz, Anna S.; Dekkers, Tanja; Bidlingmaier, Martin; Riester, Anna; Treitl, Marcus; Rhayem, Yara; Beuschlein, Felix; Lenders, Jacques W.M.; Deinum, Jaap; Eisenhofer, Graeme; et al.
Abstract : Primary aldosteronism comprises 2 main subtypes: unilateral aldosterone-producing adenoma (APA) and bilateral adrenal hyperplasia. Somatic KCNJ5 mutations are found in APA at a prevalence of around 40% that drive and sustain aldosterone excess. Somatic APA mutations have been described in other genes ( CACNA1D, ATP1A1, and ATP2B3 ) albeit at a lower frequency. Our objective was to identify genotype-specific steroid profiles in adrenal venous (AV) and peripheral venous (PV) plasma in patients with APAs. We measured the concentrations of 15 steroids in AV and PV plasma samples by liquid chromatography–tandem mass spectrometry from 79 patients with confirmed unilateral primary aldosteronism. AV sampling lateralization ratios of steroids normalized either to cortisol or to DHEA+androstenedione were also calculated. The hybrid steroid 18-oxocortisol exhibited 18- and 16-fold higher concentrations in lateralized AV and PV plasma, respectively, from APA with KCNJ5 mutations compared with all other APA combined together ( P <0.001). Lateralization ratios for the KCNJ5 group were also generally higher. Strikingly, we demonstrate that a distinct steroid signature can differentiate APA genotype in AV and PV plasma. Notably, a 7-steroid fingerprint in PV plasma correctly classified 92% of the APA according to genotype. Prospective studies are necessary to translate these findings into clinical practice and determine if steroid fingerprinting could be of value to select patients with primary aldosteronism who are particularly suitable candidates for adrenal venous sampling because of a high probability of having an APA. Abstract : Supplemental Digital Content is available in the text.